Fatty acids and recurrence of major depressive disorder: combined analysis of two Dutch clinical cohorts. (26th December 2019) - Thesing, C. S.; Lok, A.; Milaneschi, Y.; Assies, J.; Bockting, C. L. H.; Figueroa, C. A.; Giltay, E. J.; Penninx, B. W. J. H.; Ruhé, H. G.; Schene, A. H.; Bot, M.; Mocking, R. J. T.
Abstract : Objective: Omega‐3 (n‐3) and omega‐6 (n‐6) polyunsaturated fatty acid (PUFA) alterations in patients with major depressive disorder (MDD) have been shown to persist after remission. Whether these alterations are risk factors for MDD recurrence remains unknown. Here, we examined whether fatty acids predict time until MDD recurrence in remitted MDD patients. Methods: Data were used from remitted MDD patients of the Netherlands Study of Depression and Anxiety ( n  = 356) and the Depression Evaluation Longitudinal Therapy Assessment studies ( n  = 118). Associations of FAs with time until MDD recurrence up to 8‐year follow‐up were analyzed using Cox regression analyses. Study‐specific estimates were pooled using mega‐ and meta‐analysis techniques. Results: 27.5% (NESDA) and 56.8% (DELTA) participants had an MDD recurrence. Pooled results showed that no FA was significantly associated with time until MDD recurrence (n‐3 PUFAs: hazard ratio (HR) = 1.17, 95% confidence interval (CI) = 0.98–1.41, P  = 0.082; n‐6 PUFAs: HR = 1.08, 95% CI = 0.84–1.38, P  = 0.55). Conclusion: In remitted MDD patients, circulating PUFAs were not associated with prospective risk of MDD recurrence. Consequently, circulating PUFAs are unlikely to reflect a vulnerability marker for recurrence, so correcting n‐3 PUFA 'deficits' through supplementation does not seem a promising option to prevent MDD recurrence.